Greenhouse gas emission partitioning and carbon leaching in drained tropical peatland, Saratok, Malaysia - Lim, Liza Nuriati Kim Choo (2014)
Pineapple cultivation on tropical peats will lead to the release of greenhouse gases into the atmosphere and also the leaching of dissolved organic carbon once the peat is drained. Greenhouse gases need to be partitioned into microbial respiration and root respiration before deciding on whether a peat soil cultivated with pineapples are a net sink or source of atmospheric greenhouse gases as 90% of pineapples are widely grown in peat soils of Malaysia. Partitioning of carbon dioxide, methane, and nitrous oxides into root respiration, microbial respiration, and oxidative peat decomposition were achieved using a field lysimeter experiment with three treatments under controlled water table condition: (a) root respiration, microbial respiration, and peat decomposition (peat soil cultivated with Moris pineapple), (b) microbial respiration and peat decomposition (bare peat soil), and (c) peat physical oxidation due to shrinkage and consolidation (bare peat soil treated with chloroform). Dissolved organic carbon leached from peat drainage water was also quantified. The study was carried out on a drained sapric peat at the Malaysian Agricultural Research and Development Institute Peat Research Station, Saratok, Sarawak, Malaysia. Greenhouse gases emitted from the field lysimeters were measured at four hours interval for 24 hours using the closed chamber method. Flux measurements were carried during the wet (September 2012, November 2012, and January 2013) and dry (April 2013 and July 2013) seasons. Laboratory greenhouse gas emissions were also measured for pineapple roots respiration and microbial respiration using the chamber and glucose induced respiration method, respectively, to validate data from field experiments. Results from the study suggested that greenhouse gas emissions from drained peats cultivated with Moris pineapple contributed 93.4% to carbon dioxide emission, followed by 6.2% of nitrous oxide emission but with a lower methane emission at 0.3%. Microbial respiration and peat decomposition were responsible for 36% carbon dioxide emission. Pineapple roots respiration, microbial respiration, and peat decomposition contributed largely to 39% nitrous oxide emission but were responsible for 30% methane emission. Increase in dissolved organic carbon from microbial respiration and peat decomposition (235.7 mg/L) suggested rapid oxidation of organic matter through heterotrophic microbial activities. Soil carbon dioxide emissions were regulated by moderate temperature fluctuation throughout wet and dry seasons, but it was not affected by soil moisture. Nitrous oxide and methane emissions were neither affected by soil temperature nor by soil moisture. It is hoped that the findings from the study will provide improved approaches for the measurement of greenhouse gas emission in drained tropical peatland. Information obtained from partitioning respiration components will also provide insights on the possible future mitigation measures in controlling greenhouse gas emissions from drained tropical peats cultivated with pineapple.